Pengambilan Keputusan Lulusan Sekolah pada Masa Pandemi: Studi Kasus di Kampung Kejawanan - Prayoga, Dandy; Pramono, Didi (Sociology Department Of Syiah Kuala University, 2023)
This article aims to examine how school graduates during the pandemic make informed decisions between continuing their studies or entering the workforce. The research was conducted in Kampung Kejawanan using qualitative research methods. Data were collected through observation, interviews, and documentary studies. The participants consisted of high school or equivalent graduates, parents, and administrative staff during the pandemic. The findings of this study indicate that the decisions of high school graduates in Kampung Kejawanan are influenced by their rationality and interests. The economic factor is the primary consideration when choosing between pursuing further education or working. The majority of students opt to work due to financial reasons and family needs, while some choose to continue their studies based on personal interest and awareness of the importance of education. In conclusion, the decisions of high school graduates in Kampung Kejawanan regarding continuing their studies or entering the workforce are influenced by their rationality and interests, with economic factors playing a significant role. Efforts are needed to address economic disparities and improve access to education to ensure equal opportunities for children to pursue their education.AbstrakArtikel ini bertujuan untuk mengkaji bagaimana lulusan sekolah di masa pandemi membuat keputusan yang baik antara melanjutkan studi atau bekerja. Penelitian ini dilakukan di Kampung Kejawanan dengan menggunakan metode penelitian kualitatif. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Informan terdiri dari anak lulusan SMA/Sederajat di masa pandemi, orang tua, dan staf administrasi. Hasil kajian ini menunjukkan bahwa keputusan anak lulusan SMA di Kampung Kejawanan dipengaruhi oleh rasionalitas dan minat mereka. Faktor ekonomi menjadi pertimbangan utama dalam memilih antara melanjutkan studi atau bekerja. Mayoritas anak-anak memilih untuk bekerja karena alasan keuangan dan kebutuhan keluarga. Sedangkan beberapa anak memilih untuk melanjutkan studi karena minat pribadi dan kesadaran akan pentingnya pendidikan. Kesimpulannya, keputusan anak lulusan SMA di Kampung Kejawanan dalam memilih antara melanjutkan studi atau bekerja dipengaruhi oleh rasionalitas dan minat mereka. Faktor ekonomi memainkan peran penting dalam keputusan tersebut. Diperlukan upaya untuk mengatasi ketimpangan ekonomi dan akses pendidikan guna memastikan anak-anak memiliki kesempatan yang setara dalam melanjutkan pendidikan.